Mask or no mask: safety and physiological effects of wearing a surgical facemask during exercise in the COVID-19 era - Crowe, M. N. (University of Wyoming, 2021)
During the SARS-CoV-2 (COVID-19) era, facemasks (masks) have been recommended to slow/prevent viral transmission. Research on the safety and physiological effects of exercising at moderate to vigorous intensity while wearing a mask has not included direct measurement of arterial blood gases (ABG), and masks could impede normal ABG responses during exercise. Purpose: 1) Determine if it is safe to perform aerobic exercise across the light to vigorous intensity continuum while wearing a properly fitted surgical face mask - defined as normal ABG response; and 2) determine if wearing a mask during aerobic exercise increases the perception of overall exertion or breathing-specific exertion/effort. Methods: Nineteen regularly physically active participants (11 female) completed two incremental treadmill exercise tests, one baseline test not wearing a mask and the second test wearing a surgical face mask. ABG, subjective ratings of perceived exertion (RPE), and breathing effort were measured. Results: Participants (22.4±6.3 years and 22.8±2.6 kg/m2 ) completed both exercise tests. There was no statistically significant interaction for any ABG measure, indicating that the PaO2 , PaCO2, pH, TCO2 , and BE-B responses to incremental exercise were not different when wearing a mask. Breathing effort was higher at each incremental increase in exercise intensity while wearing the mask compared to no mask. Conclusions: Wearing a mask does not impact the normal/expected physiological ABG response that accompanies exercise from light to vigorous intensity. The mask does however increase participants perception of overall exertion and significantly elevates perception of breathing-specific effort as exercise intensity increases.